2013
DOI: 10.1371/journal.pone.0067976
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Myeloperoxidase Activity in Biological Samples

Abstract: BackgroundEnzymatic activity measurements of the highly oxidative enzyme myeloperoxidase (MPO), which is implicated in many diseases, are widely used in the literature, but often suffer from nonspecificity and lack of uniformity. Thus, validation and standardization are needed to establish a robust method that is highly specific, sensitive, and reproducible for assaying MPO activity in biological samples.Principal findingsWe found conflicting results between in vivo molecular MR imaging of MPO, which measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
184
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(194 citation statements)
references
References 46 publications
1
184
0
2
Order By: Relevance
“…It has been shown that hyperforin, a major component of the H. perforatum can inhibit COX-1 around 3-18 times similar to aspirin [37]. On the other hand, it has been documented that the COX-2 activity and production of inflammatory mediators by lipopolysaccharide-activated macrophage can be decreased by an ethanolic extract of H. perforatum or 4 compounds of this extract (pseudohypericin, amentoflavone, quercetin, and chlorogenic acid) [25]. It is proposed that the decrease in the activation of suppressor of cytokine signaling 3 protein (SOCS3) may partially participate in the reduction of COX-2 activity [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that hyperforin, a major component of the H. perforatum can inhibit COX-1 around 3-18 times similar to aspirin [37]. On the other hand, it has been documented that the COX-2 activity and production of inflammatory mediators by lipopolysaccharide-activated macrophage can be decreased by an ethanolic extract of H. perforatum or 4 compounds of this extract (pseudohypericin, amentoflavone, quercetin, and chlorogenic acid) [25]. It is proposed that the decrease in the activation of suppressor of cytokine signaling 3 protein (SOCS3) may partially participate in the reduction of COX-2 activity [38].…”
Section: Discussionmentioning
confidence: 99%
“…Myeloperoxidase, a peroxidase enzyme, is most abundantly found in neutrophil granulocytes and produces hypohalous acids during the neutrophil's respiratory burst and reactive oxygen production [25]. The excessive uncontrolled or inappropriate production of radical species may participate in the potentiation and prolongation of inflammatory injuries [41].…”
Section: Gross Appearance Of the Colonic Mucosa In Experimental Groupsmentioning
confidence: 99%
“…blood, plasma or tissue/cell lysates) prior to activity measurement has been utilized using different technologies [1,146] For example, Franck et al [147] developed the 'Specific Immunological Extraction followed by Enzymatic Detection' (SIEFED) method to detect MPO activity in human plasma and carotid extracts with a limit of detection of 0.08 mU/mL. The assay essentially immobilizes MPO onto a solid surface using anti-MPO antibodies, followed by addition of Amplex® Red (also known as ADHP) in the presence of H 2 O 2 and nitrite to detect MPO's peroxidase activity.…”
Section: Measuring Mpo Activitymentioning
confidence: 99%
“…This assay has been applied to human plasma after stimulation of neutrophils in whole blood [148]. Others have utilized similar antibody-capture techniques of MPO from plasma or isolated leukocytes followed by detection of chlorinating activity with APF as a substrate for HOCl [146,149].…”
Section: Measuring Mpo Activitymentioning
confidence: 99%
“…Samples were incubated at 37°C for 5 min. Next, for termination of the reaction, 50 µl of 2 M H 2 SO 4 was added and the absorbance was determined spectrophotometrically at 450 nm [15].…”
Section: Evaluation Of Mpo Activity In the Gastric Mucosal Tissuesmentioning
confidence: 99%